The association of energy or macronutrient intake in three meals with depression in adults with cardiovascular disease: the United States National Health and Nutrition Examination Survey, 2003–2018 - Hongquan Xie; Yueying Chen; Jijiao Tang; Yuteng Ma; Ying Liu; Xiyun Ren (BMC Psychiatry)
Abstract Background There is growing evidence that individuals with cardiovascular disease (CVD) are more likely to develop depression. The timing of food intake can significantly alter the body’s circadian rhythm and affect the occurrence of depression. Currently, it is unknown whether and how energy or macronutrient intake times are associated with depression in adults with CVD. Objective To evaluate dietary energy or macronutrient intake (across three meals) associations with depression in adults with CVD in a nationally representative sample. Methods The study population consisted of 3,490 U.S. adults with CVD (including 554 with depression) from the National Health and Nutrition Examination Survey 2003–2018. Energy and macronutrient intake was measured by a 24-h dietary recall, and depression was diagnosed by the Patient Health Questionnaire (PHQ-9, score ≥ 10). According to dietary energy or macronutrient intake across three meals, adults with CVD were divided into five groups. Logistic regression analysis was performed to examine associations between energy or macronutrient intake and depression after adjusting for a series of confounding factors, including age, gender, education level, household income, smoking status, drinking status, physical activity, marital status, skipping breakfast/lunch/dinner, total energy, carbohydrate, protein, dietary fiber, SFA, MUFA, and PUFA intake, T2DM and hypertension status, and BMI. Dietary substitution models were used to explore changes in depression risk when 5% dietary energy intake at dinner or lunch was substituted with energy intake at breakfast. Results When compared with participants in the lowest quintile of breakfast energy intake, those who received energy intake in the highest quintile at breakfast were associated with lower depression risk in those with CVD, and the adjusted odds ratio (OR) was 0.71 (95% CI, 0.51 to 0.91). When compared with participants in the lowest quintile of lunch or dinner energy intake, the risk of depression did not exhibit statistical significance when lunch or dinner energy intake was in the highest quintile, and the adjusted ORs were 1.08 (95% CI, 0.65 to 1.83) and 0.92 (95% CI, 0.62 to 1.37), respectively. Isocalorically replacing 5% of total energy at dinner or lunch with breakfast was associated with 5% (OR: 0.95, 95% CI 0.93 to 0.97) and 5% (OR: 0.95, 95% CI 0.93 to 0.96) lower risk of depression, respectively. Conclusions High energy intake at breakfast may be associated with a lower risk of depression in those with CVD. We should focus on the potential role of breakfast energy intake in preventing the onset of depression.